UJI DAYA HAMBAT RAMUAN HERBAL TERHADAP PERTUMBUHAN Staphylococcus aureus DAN Salmonella thypi - Muhammad Arsan Jamili; Muhammad Nur Hidayat; Amriana Hifizah (Jurnal Ilmu dan Industri Peternakan, 2014)
ABSTRACT. This study aims to : 1 ) Determine whether the herbal ingredients (onion , betel leaf , and cinnamon ) can inhibit the growth of bacteria and the bacteria S. aureus S. thypi 2 ) Knowing the long fermentation time best herbs to suppress or inhibit the growth of bacteria and bacterial S. thypi and S.aureus. Design method used is RAL 5 x 4, 5 treatments and 4 replicates for each - each test bacterium used . The treatment is carried out to test the bacteria time to see the most effective in inhibiting the growth of bacteria S. aureus and S.thypi in units of weeks. Result obtained were processed using SPSS. The results obtained from this study showed that the herb may inhibit bacterial growthinhibition test and the best herbs that herbal ingredients are fermented for 21 days (P3) can suppress the growth of S. thypi bacteria’s . In other words , P3 significantly different from P0 , P1 , P2 , and P4 ( P <0.05) . As for the bacteria S. aureus , which is a good herb to inhibit the growth of S. aureus bacteria fermented herbs either 1 week (P1) , 2 weeks (P2) , 3 weeks ( P3 ) and 4 weeks ( P4 ) . Or in other words , each of these treatments has nosignificant difference in inhibiting the bacteria S . aureus . The treatment is said to becapable of inhibiting bacterial growth due in accordance with the standards of the Ministry of Health on scale power resistor material used is 12 mm . The materials used in this study according to treatment had a greater inhibition than the prescribed limit ( P < 0.05 ).